Self-Assembly of Nanostructures and Patchy Nanoparticles - Mehraeen, Shafigh (IntechOpen, 2020)
Top-down approaches are currently the main contributor of fabricating microelectronic devices. However, the prohibitive cost of numerous technological steps in these approaches is the main obstacle to further progress. Furthermore, a large number of applications necessitate fabrication of complex and ultra-small devices that cannot be made using these approaches. New approaches based on natural self-assembly of matter need to be developed to allow for fabrication of micro and nanoelectronic devices. Self-assembly of nanostructures is a dynamic field, which explores physics of these structures and new ways to fabricate them. However, the major problem is how to control the properties of the nanostructures resulting from low dimensionality. This book presents recent advances made to address this problem, and fabricate nanostructures using self-assembly.